KOORDINASI PEMERINTAH DAERAH DALAM PEMBANGUNAN JALAN DI KECAMATAN SALIBABU KABUPATEN KEPULAUAN TALAUD Coordination Of Local Government In Road Construction In Kecamatan Salibabu Kabupaten Kepulauan Talaud - Majore, Nona; Rompas, Welson Yappi; Mambo, Rully (JURNAL ADMINISTRASI PUBLIK, 2017)
AbstractThe purpose of this study is to know how the coordination of local goverment in road constructionin the District of Salibabu Talaud Islands Regency.This research uses the qualitative method. Data collection by interview technique: while dataanalysis using qualitative analysis techniques interactive model of Miles and Hubernann.Based on research results drawn conclusions: (1) Coordination of district road constructionplanning in sub-districts of Salibabu run orderly and smoothly in accordance with the mechanism that hasbeen set in UU.No.25 Tahun 2004 about The National Development Planning System. Related governmentinstallations (Dinas PUTR, Bappeda, and Camat) coordinate well so that the district road developmentprogram can be set according to the priority scale. Coordination mechanism of district road developmentplaning in Salibabu sub-distric implemented accordingto the bottom. (2) Coordination of local government(Dinas PUTR and Camat, and also with Kepala Desa) in the implementation of road construction programsor projects in the District of Salibabu Talaud Islands Regency well done and running smoothly.Key Words : Coordination, Local Government, Road Construction,